Gallic Acid as Corrosion Inhibitor for Aluminum 6061 in Alkali Solutions - Ali, Enas Hussien; Himdan, Takialdin A.; Ahmed, Zainab W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
The research aims to study the corrosion of aluminum alloy(6061) in 0.6 mol. dm-3 NaCl solution in base medium  was examined with out and with Gallic acid as environmentally â€“ friendly corrosion inhibitor at temperature range (298-313)K. The inhibitive action of gallic acid on corrosion of aluminum alloy(6061)  in KOH solution was examined through electrochemical polarization method using potentiostatic technique and surface analysis by optical microscopy,  Polarization measurements indicate that the examined compound act as a mixed type inhibitor. Results appeared that the inhibition occurs through adsorption of the inhibitor molecules on the metal surface and it was obeyed Langmuir adsorption isotherm. Some thermodynamic parameters activation energy  were calculated to elaborate the mechanism of inhibition. The surface characteristic of the inhibited and uninhibited metal samples were examined by optical microscopy.